Recent advances in drug delivery of celastrol for enhancing efficiency and reducing the toxicity - Sun, Yuan; Wang, Chengen; Li, Xiaoguang; Lu, Jun; Wang, Maolin (Frontiers in Pharmacology, 2024)
Celastrol is a quinone methyl triterpenoid monomeric ingredient extracted from the root of Tripterygium wilfordii. Celastrol shows potential pharmacological activities in various diseases, including inflammatory, obesity, cancers, and bacterial disease.However, the application prospect of celastrol is largely limited by its low bioavailability, poor water solubility, and undesired off-target cytotoxicity. To address these problems, a number of drug delivery methods and technologies have been reported to enhance the efficiency and reduce the toxicity of celastrol. We classified the current drug delivery technologies into two parts. The direct chemical modification included neucleic acid aptamer, neucleic acid aptamer-dendrimer and glucolipid. The indirect modification contained dendrimer, polymer, albumin and vesicular carrier. The current technologies could covalently or encapsuled the celastrol, which improved its selectivity. Here, we present the review that focalizes the recent advances of drug delivery strategies in enhancing efficiency and reducing the toxicity of celastrol.